2012
DOI: 10.3109/02688697.2012.732716
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness and tolerability of vagal nerve stimulation in adults with intractable epilepsy: a retrospective analysis of 100 patients

Abstract: Data for 100 vagal nerve stimulation (VNS) patients were collected and analysed retrospectively. The mean seizure reduction was 17.86% (n = 67) at 6 months, 26.21% (n = 63) at 1 year, 30.43% (n = 53) at 2 years, 48.10% (n = 40) at 3 years, 49.44% (n = 32) at 4 years, 50.52% (n = 35) at 5 years, 45.85% (n = 31) at 6 years, 62.68% (n = 25) at 8 years, 76.41% (n = 9) at 10 years, 82.90% (n = 4) at 12 years. Evidence of statistical significance for mean seizure reduction over time was strong with all p values less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 23 publications
1
19
0
3
Order By: Relevance
“…Post-VNS AED requirement exhibited a decreasing trend with 13.5%, 32.4% and 24.3% of patients requiring one, two and three AEDs, respectively. Non-significant reductions in AEDs were also reported by Ching et al 16 with VNS (AEDs prescribed reduced from 3.29 to 3.12, p>0.05).…”
Section: Comparative Review Resultsmentioning
confidence: 50%
See 3 more Smart Citations
“…Post-VNS AED requirement exhibited a decreasing trend with 13.5%, 32.4% and 24.3% of patients requiring one, two and three AEDs, respectively. Non-significant reductions in AEDs were also reported by Ching et al 16 with VNS (AEDs prescribed reduced from 3.29 to 3.12, p>0.05).…”
Section: Comparative Review Resultsmentioning
confidence: 50%
“…Progressive improvement in seizure control has been reported (table 1) by demonstrating increasing responder rates (VNS,14 CRS13 and ANT-DBS12) and by decreasing median/mean seizure frequency from baseline over time (VNS,14 16 CRS13 and ANT-DBS12). Different rates of seizure freedom for at least 6 months were noted in all forms of neurostimulation, although none of these studies reported rates of seizure freedom throughout the follow-up period (table 2).…”
Section: Comparative Review Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Infections requiring device removal occur in 1.6% of patients [9]. Overall VNS mortality is between 1 and 3.9% [9, 10]. …”
Section: Introductionmentioning
confidence: 99%